THE ROLE OF INTERNATIONAL HOTEL BUSINESS IN GLOBAL ECONOMY AND FEATURES OF DEVELOPMENT - Doniyor Tursunov (TADQIQOTLAR, 2025)
Abstract. The international hotel business plays a significant role in shaping the global economy by facilitating tourism, creating employment opportunities, and fostering cross-cultural exchange. As one of the most dynamic sectors of the service industry, hotels contribute to GDP growth, attract foreign investment, and stimulate the development of related industries such as transportation, catering, and entertainment. In recent decades, globalization has accelerated the expansion of international hotel chains, enabling standardized services, technological innovation, and sustainable practices across diverse markets. This study analyzes the economic impact of the international hotel business, highlighting its contribution to national competitiveness and regional development. It also examines key features of the sector’s evolution, including digital transformation, ecological responsibility, and the growing demand for personalized guest experiences. The findings suggest that the international hotel industry is not only a driver of economic growth but also a catalyst for cultural integration and sustainable development in the global economy.